MARITAL INSTABILITY IN A MUNICIPALITY OF THE SOUTH OF ITALY - Sacco, Giuseppina; Sacco, Pietro (European Scientific Journal, ESJ, 2014)
The purpose of this study is to highlight the common and determining elements of marital instability in the first years of marriage in the municipality of Bari, for a comparison on a national level. More specifically, the objective was to verify whether the city of Bari shares the trend which is well established in the rest of Italy towards the so-called â€œlightening marriagesâ€, by which is intended the interruption of the marriage in its first years. We started from the basic data formed by the time series of first marriages and separations according to the years in which the weddings took place. The separations examined here by means of longitudinal analysis involve cohorts of marriages formed in two five-year periods (the late 20th century, 1985-1989) and the beginning of the 21st century, 2001-2005) held to be of some significance in showing the modifications in the institution of marriage which took place over a period of more than twenty years. The analyses of the data provided interesting results. For example, it was observed that with the passage of time the comparison of the two five-year periods indicates that the consensual initiative is adopted by almost all the couples who decide to separate, because it is simpler, less expensive, and is concluded more quickly. There is also a marked tendency to separate in the first years of marriage and the type of marriage rites definitely does not have any influence on the way in which the marriage breaks own.